Spectrum of Social Studies: Testing of the Social Reconstruction Vygotsky's Paradigm in Elementary Schools Social Studies Learning - Lasmawan, I Wayan (JPI (Jurnal Pendidikan Indonesia), 2019)
In General, this research aimed to develop new formula of ideas and hypotheses of social science education curriculum of primary school. The Development was done through the integration of the principles of social reconstruction and constructivism of Vygotsky in interactional construction. This research used the design of development research, conducted in Bali Province by involving education experts, principals, teachers, and primary school students as research samples determined by purposive-randomization. The data instruments of this research consisted of observation sheets, interview guides, questionnaires, and test of learning outcomes. The whole research data was analyzed qualitatively with an interactive cycle model and CAR (contextuality-accuracy-relevancy) model, combined with quantitative analysis to comparatively graded the advantage of social reconstruction design with conventional learning design in social science education of primary school. The result of the study indicated that: (1) the social science competency which allowed for students of primary school in accordance with the social constructivism design of Vygostky consisted of : personal competence, sociocultural, and intellectual competence, (2) the relevant social science material structure to develop was when systematically organized as real pedagogical learning experiences, sociocultural, psychologycal by relied on the principle of â€œa studentâ€™s as a psychological, sociocultural, and intellectual horizons reconstructions -basedâ€, and (3) social science classroom environment was a psychological and sociocultural context that should be laid out and directed at efforts of : (a) dynamization of student position from natural position to sociocultural position; (b) provide facility and personal and sociocultural mediation to students in their endeavors to reconstruct the contents, functions, and operations contained within their personalities structure.